Capture of a Transition State Using Molecular Dynamics: Creation of an Intercalation Site in dsDNA with Ethidium Cation - Monaco, Regina R. (Journal of Nucleic Acids, 2010)
The mechanism of intercalation and the ability of double stranded DNA (dsDNA) to accommodate a variety of ligands in this manner has been well studied. Proposed mechanistic steps along this pathway for the classical intercalator ethidium have been discussed in the literature. Some previous studies indicate that the creation of an intercalation site may occur spontaneously, with the energy for this interaction arising either from solvent collisions or soliton propagation along the helical axis. A subsequent 1D diffusional search by the ligand along the helical axis of the DNA will allow the ligand entry to this intercalation site from its external, electrostatically stabilized position. Other mechanistic studies show that ethidium cation participates in the creation of the site, as a ligand interacting closely with the external surface of the DNA can cause unfavorable steric interactions depending on the ligands' orientation, which are relaxed during the creation of an intercalation site. Briefly, such a site is created by the lengthening of the DNA molecule via bond rotation between the sugars and phosphates along the DNA backbone, causing an unwinding of the dsDNA itself and separation between the adjacent base pairs local to the position of the ligand, which becomes the intercalation site. Previous experimental measurements of this interaction measure the enthalpic cost of this part of the mechanism to be about −8 kcal/mol. This paper reports the observation, during a computational study, of the spontaneous opening of an intercalation site in response to the presence of a single ethidium cation molecule in an externally bound configuration. The concerted motions between this ligand and the host, a dsDNA decamer, are clear. The dsDNA decamer AGGATGCCTG was studied; the central …GATG… site was the intercalation site.